MODEL RESILIENSI NAFKAH RUMAHTANGGA PETANI PADI RAWA LEBAK DALAM MENGHADAPI PANDEMI COVID-19 - Indri Januarti (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to (1) analyze the structure of the household income of farmers during the covid-19 pandemic; and (2) analyze the household resilience of rice farmers in the Lebak swamp land and the factors that influence it. The research method used is a survey method with a sample of 60 rice farmers, which are divided into 2 strata, IP100 and IP200 farmers. The data analysis used for the first purpose is descriptive analysis method with tabulation, while the second objective uses multiple regression analysis. The results showed that the household income structure of the Lebak swamp rice farmers during the Covid-19 pandemic, both IP100 and IP200, was obtained from income from rice farming and outside farming, such as trade, iron welders and construction workers. From the research results, it can also be seen that the IP100 and IP200 farmers' resilience levels are relatively the same, namely in the high and medium categories. This is because the dominant source of livelihood is obtained from rice farming which in less than six months has harvested or generated income. The forms of livelihood resilience carried out by rice farming households in the Lebak swamp land include the use of savings, the use of social capital and the use of remittances. From the results of multiple linear regression analysis, it can be seen that there are three variables that significantly influence the level of household livelihood resilience of rice farmers in the Lebak swamp land, namely the farming experience variable, the farmer group membership dummy and the cropping index dummy.